PENGARUH ACTIVITY, INTEREST, OPINION (AIO) DAN PERSEPSI HARGA TERHADAP KEPUTUSAN MENONTON FILM DI BIOSKOP E-PLAZA SEMARANG - Ratri Lalitamanik; Apriatni Endang Prihatini; Reni Shinta Dewi (Universitas Diponegoro, 2014)
This research was motivated by fact that there’s a decline in consumers interest to watch movies in E-Plaza cinema since there’s new competitor emerged in Semarang, affected by lifestyle and price perception factors. This research is aimed to test the influence of activity, interest, opinion (AIO), and price perception towards consumers’ decision to watch movies at E-Plaza cinema Semarang. 100 people in Semarang were chosen as sample by non-probability sampling technique. Linear regression analysis and significance test were used to test the hypotheses using SPSS 17.0. The study results indicate that partially; activity has no influence towards consumer decision, whereas interest and opinion, in spite of having low effects, still has positive influence towards consumer’s decision. Price perception, as the biggest influencer, has positive and significant influence towards consumers’ decision. Simultaneously, activity, interest, opinion and price perception influences consumer’s decision at 48,1%.